Analisis Campur Kode dalam Film Imperfect Season 2 Episode 1–5 - Alda Misqola Habah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Language variation in the form of mixed code is a linguistic symptom that is often found in bilingual and multilingual communities, especially in popular media such as movies. This study aims to identify and describe the mixed forms of code that appear in the second season of the Imperfect: The Series series, specifically in episodes 1 to 5. This study uses a qualitative descriptive approach with data collection techniques in the form of recording and analysis of dialogues between figures that contain mixed elements of code. The research instrument is in the form of dialogue transcripts that are analyzed with a sociolinguistic approach, mainly based on the theory of mixed code according to Suwito (1985) and the theory of relevance of the social context according to Holmes (2013). The results of the study revealed two main categories of forms of code mixing, namely inner code mixing involving elements of regional languages, and outer code mixing which includes the insertion of words or phrases from foreign languages, such as English. Based on data analysis, it was found that there were 12 data mixed in code and 18 data mixed in code out. This phenomenon shows that the use of mixed codes in character dialogue not only serves as a marker of social and cultural identity, but also as a reflection of the dynamics of communication in a pluralistic and modern urban society. In addition, the use of mixed codes in audiovisual media also has pragmatic and aesthetic implications, which can strengthen character characterization, create humorous effects, adjust the context of social situations, and increase narrative appeal to young audiences who are familiar with multilingualism.